Pembangun Karakter Guru Beretika Islami untuk Peningkatan Profesionalisme di Era Digital - Rahman Tanjung; Rian Permana; Rini Novianti Yusuf; Fadli Rais; Saepudin (Bulletin of Community Engagement, 2024)
The character of teachers with Islamic ethics is very important in increasing educational professionalism, especially in the digital era which is increasingly developing rapidly. The aim of this community service activity is to build the character of teachers at Madrasah Ibtidaiyah  in the Tegalwaru District area who are able to integrate technology with Islamic values in learning. The method used is the Asset-Based Community Development (ABCD) approach, where teachers are actively involved in every process of planning and implementing activities. This activity includes training in the use of learning technology, discussions on the application of Islamic ethics in a digital context, as well as direct assistance in its implementation in the classroom. The results of this activity show an increase in teacher competence in using technology for learning, with 75% of teachers feeling more confident in using technology. In addition, there is a better understanding of the importance of integrating Islamic values in digital learning. This program was also successful in creating social change by forming a teacher study group that continued Islamic technology-based learning independently. The implication of this activity is the need for ongoing training and the development of a more structured learning community to support the development of teacher professionalism in the future.